Implementasi Manajemen Peserta Didik Program Tahfidz Santri Putra Pondok Pesantren Darussalam Blokagung Banyuwangi Dalam Minat Tilawatil Quran - Ikhsan Huzali; Moh. Fathul Ikhsan (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
Teaching the Al-Quran in Islamic boarding schools really needs special activities or programs in order to meet the demands of Islamic education in education, especially in Islamic boarding schools. This research seeks to examine how the Tahfidz Al-Quran program is implemented in Islamic boarding schools and its impact on students' interest in Tilawatil Quran activities, referring to Al-Quran teaching models in Islamic boarding schools including methods, strategies and delivery. This type of research is qualitative and as a concept development model, data collection techniques include observation, interviews and documentation. Data analysis uses triangulation and data reduction, and conclusions. The results show that efforts to implement the tahfidz program at the Darussalam Islamic Boarding School Blokagung Banyuwangi will attract students' interest in Al-Quran recitations if it is packaged with several supporting things including good teacher competence, physical and non-physical support, interesting teaching methods, and collaboration. between students and good teachers, and also the tahfidz guidebook that is used as a reference must be clear. This will attract students' interest in Tilawatil Quran activities